2018
DOI: 10.3389/fimmu.2018.02427
|View full text |Cite
|
Sign up to set email alerts
|

Complement Component C1q as Serum Biomarker to Detect Active Tuberculosis

Abstract: Background: Tuberculosis (TB) remains a major threat to global health. Currently, diagnosis of active TB is hampered by the lack of specific biomarkers that discriminate active TB disease from other (lung) diseases or latent TB infection (LTBI). Integrated human gene expression results have shown that genes encoding complement components, in particular different C1q chains, were expressed at higher levels in active TB compared to LTBI.Methods: C1q protein levels were determined using ELISA in sera from patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 46 publications
2
51
1
1
Order By: Relevance
“…IgG1 and IgG3 subclasses are also the main antibodies capable of activating complement (119). Consistent with these associations, complement C1q levels are higher in active TB compared to latent TB, and complement cascade molecules are upregulated 18 months before progression from Mtb infection to TB disease (120)(121)(122). Moreover, some monoclonal Mtb IgG1 can enhance bacterial replication in vitro, demonstrating the potential to exacerbate disease (27).…”
Section: Antibody Isotypes and Subclasses In Mycobacterium Tuberculosmentioning
confidence: 68%
“…IgG1 and IgG3 subclasses are also the main antibodies capable of activating complement (119). Consistent with these associations, complement C1q levels are higher in active TB compared to latent TB, and complement cascade molecules are upregulated 18 months before progression from Mtb infection to TB disease (120)(121)(122). Moreover, some monoclonal Mtb IgG1 can enhance bacterial replication in vitro, demonstrating the potential to exacerbate disease (27).…”
Section: Antibody Isotypes and Subclasses In Mycobacterium Tuberculosmentioning
confidence: 68%
“…22 Furthermore, increased expression of mRNA for complement component C1q has been described in peripheral blood cells from active TB patients. [23][24][25] More recently, Lubbers et al reported elevated serum C1q levels in APTB as compared to LTBI, healthy controls, and disease controls. 23 Consequently, serum C1q was proposed as biomarker to detect active TB disease.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] More recently, Lubbers et al reported elevated serum C1q levels in APTB as compared to LTBI, healthy controls, and disease controls. 23 Consequently, serum C1q was proposed as biomarker to detect active TB disease. 23 However, Lubbers et al did not explore serum C1q levels in relation to TB-associated uveitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C1QB encodes a component of the complement 1 (C1Q) complex, part of the complement immune system. Expression of genes encoding components of C1Q have been shown to correlate with the progression of active TB compared to HC and LTBI cohorts [42] and a recent study showed that, in four independent cohorts, components of the C1Q complex are elevated in patients with active TB compared to those with LTBI [43]. ZNF296 encodes a member of the C2H2 zinc-finger protein family, which contain DNA binding motifs often found in transcription factors.…”
Section: Discussionmentioning
confidence: 99%